Heat conduction across non-ideal interfaces between dissimilar metals - Yeo, Kheng Huang (2014)
Heat conduction across dissimilar materials will be considered in this report. Fourier series expansion will be used to derive the equations that will be further expressed into three different interfaces; perfect, low-conducting and high conducting. A Matlab program will be written to simulate two cases with varying boundary conditions such as constant heat rate and temperature. Additionally, the report will look into what conditions are necessary for the low-conducting and high-conducting interfaces to display similar heat conducting abilities as the perfect interface. All results will be compared and evaluated with the help of detailed tables and graphs.